Outcome of Volar Plate in Patients with Intra Articular Distal Radius Fracture - Muhammad, Gul; Shahwani, Muhammad Bakhsh; Khan Ghilzai , Asad; Shah Jamal; Kakar , Khushal Khan; Muhammad Luqman; Khan , Ainuddin; kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Intra-articular variations of distal radius fractures, which are common orthopedic injuries, might make it difficult to achieve anatomical reduction and functional rehabilitation. Because of its durability, capacity to restore joint congruity, and ability to facilitate early mobilization, volar plate fixation is the recommended technique. Objective: The purpose of this study is to assess the radiological, functional, and clinical results of volar plate fixation in intra-articular fractures of the distal radius. Methodology: At a Quetta tertiary care hospital, a cross-sectional study was carried out between August 2022 and August 2024. Included were 55 adult patients who had displaced intra-articular fractures of the distal radius. The AO system was used to classify the fractures, and volar locking plates were used to cure them. The Modified Mayo Wrist Score was used to measure functional outcomes, and follow-ups at two, six, three, and six months were used to gauge union time and complications. Results: The most prevalent fracture type (41.8%) was AO type 23-C2, and the mean age was 37.2 ± 10.05 years. With a mean duration of 11.98 ± 1.64 weeks, union was attained in 98.2% of patients. With 67.2% reporting good results and 27.2% reporting very good results, the functional outcomes were positive. There were just a few complications, such as median nerve neuropathy (1.8%), wound dehiscence (3.6%), and superficial infections (11%). Conclusion: volar plate fixation is a successful treatment for intra-articular distal radius fractures because it has minimal complication rates, good union rates, and functional results.